Metastatic Prostate Cancer Diagnosed by Bone Marrow Aspiration in an Elderly Man Not Undergoing PSA Screening - Alam, Ridwan (Urol Case Rep, 2017)
Prostate cancer screening by PSA testing remains controversial, particularly in the elderly. Practice guidelines from most clinical societies suggest discontinuing PSA screening at age 70 while the USPSTF recommends against screening at any age. Recent reports have demonstrated an increased incidence of metastatic prostate cancer, with men aged 75 or older accounting for roughly half of those newly diagnosed at an incurable stage. We herein describe the case of an elderly gentleman with no history of prostate cancer screening who presented with anorexia and back pain of unclear etiology. Evaluation with bone marrow aspiration revealed a diagnosis of metastatic prostate cancer.